Tightness Assessment of Bolted Flange Connections Considering the Creep Effect of Gasket. (2015) - Cheng, Y.; Zheng, X.T.; Yu, J.Y.; Xu, J.M.; Wang, C.G.; Lin, W.
Abstract: The tightness of bolted flange connections is the important guarantee to meet the safety operation for a long period, the creep effect of gasket may affect the tightness of bolted flange connections under high temperature conditions due to its creep deformation. Considering the creep effect of metal flexible graphite composite gasket under high temperature, the deformation compatibility equation of bolted flange connection system was deduced. The time-dependence of flange rotation, the gasket deformation and the gasket contact stress were studied systematically. Moreover, the influencing factors of leakage rate were analyzed in detail. Finally, based on the theory of tightness, the safety assessment method due to leakage rate was constructed under high temperature. Results presented the gasket stress increases linearly from inside to outside and the gasket stress became lower and lower with the creep time extended. The time-dependent leakage rate of bolted flange connections was deduced, and the tightness assessment can be made conveniently according to the proposed method.